Examining lifeguards' abilities to anticipate surf hazard instigators – An exploratory study. (November 2021) - Meir, Anat; Hartmann, Daniel; Borowsky, Avinoam
Highlights: Lifeguards' ability to perceive hidden potential surf hazards is rarely studied. We studied surf hazard perception by exploring responses and eye-movements data. Surf lifeguards identified morphodynamic features as potential hazard instigators. Professional swimming-pool lifeguards and control were more focused on the bathers. Implications for public health policies and public safety education are discussed. Abstract: Being swept by rip currents is the leading cause of most beachgoers drowning on surf beaches worldwide. Lifeguards have a crucial role in protecting and saving beachgoers in distress. Although most surf lifeguards' activities are preventative, only few studies have systematically investigated their awareness of latent hazardous surf situations that might be missed by layman patrons. This study was aimed at exploring beach-related hazard perception skills of surf lifeguards, swimming-pool lifeguards, and patrons who served as control. Participants were exposed to twenty-nine, 10 s long video clips, depicting real-world hazardous surf situations footage taken along Israeli Mediterranean beaches from a lifeguard tower perspective. While observing each video clip, participants were asked to press a response button in case they identify a surf situation that may pose a drowning threat for bathers. Eye-movement data and behavioral response were examined. The results showed that surf lifeguards were much more aware of morphodynamic features in the nearshore area (e.g., rip currents) than any other group. Furthermore, professional swimming-pool lifeguards and control were more focused on the bathers themselves, regardless of the nearshore state and its morphodynamic characteristics. These findings emphasize that experience enables surf lifeguards to perceive morphodynamic conditions of the surf, integrate these elements with bathers' dynamics, and holistically predict future hazardous situations. Exploring and demonstrating bathers' knowledge deficiencies in evaluating key, life-threatening rip currents as surf Hazard Instigators (HIs) may help in producing public education programs as an effective drowning prevention technique. Implications for public health policies are discussed.